Social framing effects in leadership by example: Preferences or beliefs? - Cartwright, Edward; Drouvelis, Michalis (Economic Inquiry, 2024)
We study the impact of framing on leading‐by‐example. Our 2 × 2 design consists of group level frames (Wall Street vs. Community) and individual level frames (First/Second Movers vs. Leader/Followers). We report on two studies where we elicit participants' beliefs allowing us to evaluate whether framing effects are driven by beliefs or preferences. Across both studies, average contributions are significantly lower in the Community—First Mover frame. This is primarily because leaders contribute less, pulling down followers' contributions. We find that contributions are strongly related to first order and second order beliefs but framing effects remain once we control for beliefs.